2005
DOI: 10.1002/ajpa.20204
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal timing, hormones, and body composition among adolescent Turkana males

Abstract: The Turkana, like other East African pastoral groups, are known for their tall adult stature, achieved despite a blunted growth spurt during adolescence and continued growth into the early 20s. To investigate the hormonal mechanisms associated with the pattern of slow and continued adolescent growth, we collected data on hormonal status, height, weight, and trunk skinfolds and ethnographic self-reports of testicular maturation in a cross-sectional sample of 35 nomadic and 37 settled Turkana males aged 14-24. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Boys also presented very slow growth during pubescence (Benefice 2007). A similar late onset of puberty was observed in other African groups, including the Turkana and Karamajong of Eastern Africa (Campbell et al 2005,Gray et al 2004). …”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Boys also presented very slow growth during pubescence (Benefice 2007). A similar late onset of puberty was observed in other African groups, including the Turkana and Karamajong of Eastern Africa (Campbell et al 2005,Gray et al 2004). …”
Section: Introductionsupporting
confidence: 77%
“…A G2 stage of around 9.2 to 10.03 was observed in the NHANES III study (Sun et al 2002). This delay in puberty onset is concomitant with a very low level of blood testosterone (Campbell et al 2005). In girls, age at first menstruation was estimated by Sandra Gray to be 16.5 years.…”
Section: Slow Growth and Maturation Rates In Senegal Resulting In A "mentioning
confidence: 92%
See 1 more Smart Citation
“…Sensitivity to such environmental stresses is higher in preadolescent ages than in adolescent or adult ages (Bogin, 1999;Frisancho et al, 1980;Johnston and Beller, 1976). Some studies have shown that delayed growth in preadolescence due to nutritional stress was followed by compensatory gain in adolescence (Kulin et al, 1982;Pawloski, 2003), while it has commonly been recognized that environmental stress such as helminth infection and malnutrition tends to reduce the maximal potential responses of bone, muscle, and fat tissues to hormonal function that determines adolescent growth, thereby hampering the compensatory gain (Cameron et al, 1993;Campbell et al, 2005;McGarvey et al, 1992).…”
mentioning
confidence: 99%
“…In part because of the lack of a visible marker of puberty such as menarche, studies of the population variation in age at puberty of boys are much more limited than those for girls (Zemel et al, 1993;Panter-Brick et al, 1996;Campbell et al, 2004). Energy deficiency has been associated with later ages at puberty in Kenyan and Zambian boys, as measured by pubertal hormone changes (Campbell et al, 2005). Energy deficiency has been associated with later ages at puberty in Kenyan and Zambian boys, as measured by pubertal hormone changes (Campbell et al, 2005).…”
Section: Pubertymentioning
confidence: 99%